Ultrasound of the Radial Nerve: A Pictorial Review. (25th February 2021) - Becciolini, Marco; Pivec, Christopher; Raspanti, Andrea; Riegler, Georg
Abstract : This pictorial review focuses on the ultrasound (US) appearance of the normal and pathological radial nerve (RN) and its branches and provides tips with which to locate them and avoid misinterpretation of normal findings. A wide range of our pathological cases are reviewed and presented to help in familiarizing the reader with common and uncommon clinical scenarios that affect the RN and its main branches.